1996
DOI: 10.1063/1.117889
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology of laser deposited diamondlike films by atomic force microscopy imaging

Abstract: The surface morphologies of diamondlike carbon (DLC) films with atomic force microscopy (AFM) are reported. The films were prepared by laser ablation with tuning power densities range from 3×108 to 1×1010 W/cm2. For power densities above 2×109 W/cm2, the films reveal smooth surfaces with uniform shapes of nanometer sized carbon clusters (sp3 bonding) and retain the surface roughness of the silicon substrate. For power densities below that, graphitic films are formed, and the surface roughness increases with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…From a side view, we observe that they are a little rougher than those of slab model I. This observation is consistent with the earlier experimental measurement by Park et al 25 They found that among the films grown under different conditions, those with higher sp 2 contents are rougher.…”
Section: Surface Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…From a side view, we observe that they are a little rougher than those of slab model I. This observation is consistent with the earlier experimental measurement by Park et al 25 They found that among the films grown under different conditions, those with higher sp 2 contents are rougher.…”
Section: Surface Structuresupporting
confidence: 92%
“…There are still extensive discussions in experimental works about the growth mechanisms of ta-C thin films. [23][24][25][26] In this paper, we report our recent study of a model surface structure of ta-C thin films. Understanding properties of the static, equilibrium structure of surface is an essential precursor to understanding growth.…”
Section: Introductionmentioning
confidence: 99%
“…Але загалом досліджуються (в основному експериментально) особливості або окремих речовин, що опромінюються (кремній [10], алюміній [2], сталь [3], графіт [11], титан [12], срібло [13], мідь [14], алмаз [15]), або імпульсний вплив, обмежений по енергії імпульсів різної тривалости [2,3]. Велику кількість робіт присвячено дослі-дженням наслідків впливу імпульсів різної тривалости [10].…”
Section: мета і завдання дослідженняunclassified
“…[1][2][3][4] A clear correlation between surface morphology and the degree of diamond-like carbon properties was shown. 1,2 Due to the high compressive stress in the DLC films, DLC films with a hardness value of 40 GPa usually peel off the silicon substrates when the thickness of the films exceeds 200 nm. 5,6 In our previous report, a compositiongraded intermediate layer was used to relax the stress.…”
Section: Introductionmentioning
confidence: 99%